الإنفاق العام ودوره في تعزيز التنمية الاقتصادية دراسة حالة التجربة الماليزية - زيزفون عزة (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The Malaysian experience realized the importance of public expenditure as one of financial policy tools used in the process of economic development, because it helps in increasing the productive capacity of the economy if it was directed properly to the important sectors in the economy, and public expenditure is the main growth engine of the economic. The Malaysian experience developed a long-term growth plans and put all its different types of resources in the service of these goals by allowing foreign investments enter their economy and direct those investments to suit their own plans for the economic development process. The Malaysian government has also largely focused on training local workforce as well as the development of its internal resources and aid low-income workers. To be successful in achieving its objectives in the field of economic development, the Malaysian administration believed that it is necessary to work on the consolidation of security and political stability in the country because of its direct impact on the economic life. The Malaysian government has been successful in its experience thanks to its proper planning and utilization of all available resources that helped in the transition from a normal country to become one of the advanced and influential countries in the global economy. أيقنت التجربة الماليزية بأهمية الانفاق العام كواحد من أدوات السياسة المالية المستخدمة في عملية التنمية الاقتصادية لأنه يسهم في زيادة القدرات الإنتاجية للاقتصاد إذا وجه بصورة صحيحة نحو القطاعات المهمة في الاقتصاد فالانفاق العام يعتبر المحرك الاساسي للنمو الاقتصادي. قامت التجربة الماليزية بوضع خطط تنموية طويلة الأجل وتسخير كافة مواردها المختلفة في خدمة هذه الأهداف، وذلك من خلال السماح للاستثمارات الأجنبية في الدخول إلى الاقتصاد والقيام بتوجيهها لتتناسب مع الخطط الخاصة بها من أجل عملية التنمية الاقتصادية. كما اهتمت الحكومة الماليزية وبشكل كبير بتدريب اليد العاملة المحلية بالإضافة إلى تنمية وتطوير الموارد الداخلية وتوجيه المساعدات لأصحاب الدخل المحدود. ولكي تنجح في تحقيق أهدافها في مجال التنمية الاقتصادية آمنت الإدارة الماليزية بأنه لا بد من العمل على ترسيخ الاستقرار الأمني والسياسي في البلاد لما له من آثار مباشرة على الحياة الاقتصادية. وقد نجحت تجربة الحكومة الماليزية بفضل تخطيطها السليم والاستغلال لكافة الموارد المتاحة في الانتقال من دولة عادية لتصبح في مصافي الدول المتقدمة والمؤثرة على الاقتصاد العالمي.